Interactive effects of chronic nitrogen addition and pulsed deluge events on community structure and function of the shortgrass steppe - Linabury, Mary C., author; Smith, Melinda D., advisor; Blumenthal, Dana, committee member; Havrilla, Caroline, committee member; Nippert, Jesse, committee member (Colorado State University. Libraries, 2025)
Global change is intensifying climate extremes, leading to more intense droughts and deluges (i.e., large rainfall events). Simultaneously, mass industrialization has led to the continuous alteration of resources such as atmospheric CO2 and reactive nitrogen. Patterns of perturbations can be evaluated through the "pulse-press" framework which describes resource alteration along a temporal continuum: from discrete, short-term "pulse" to chronic, long-term "press". The combination of chronic press and discrete pulse resource alterations is expected to cause large and potentially unexpected changes to ecosystem structure (i.e., diversity, community composition) and function (i.e., productivity). Pulse-press dynamics have been observed and explored in theory and models, but robust experimental evidence is lacking. Therefore, this dissertation experimentally evaluated pulse-press dynamics in two grassland ecosystems: a shortgrass steppe in northeastern Colorado and a tallgrass prairie in northeastern Kansas. The first chapter of this dissertation established how the two grassland ecosystems responded to five years of nitrogen press along a gradient of addition levels. Within the shortgrass steppe, I found that nitrogen addition did not affect productivity but caused community change. In contrast, production increased within the tallgrass site without changes in community composition. These divergent responses, likely mediated by site-level differences in aridity, demonstrate that structural and functional responses may decouple under nitrogen press. The second chapter examined the interaction of pulsed deluge timing and nitrogen press at the shortgrass steppe. An extreme deluge applied mid-late growing season in 2021 had no significant effect on structure or function, while an early-mid deluge in 2022 synergistically interacted with nitrogen addition resulting in large increases to production. This synergistic interaction was driven by an increase in a weedy forbaceous species and showed that nitrogen press and pulsed deluge events can generate unexpected effects on ecosystem function. The third and final chapter of this dissertation assessed the legacy effects of deluge pulse amid ongoing nitrogen press. We monitored post-deluge plots and found unexpected production legacies that were not predicted by the initial response to deluge but were influenced by growing season precipitation. Community composition changes persisted even during the dry 2024 growing season, when production legacies were no longer evident. These results demonstrate that effects of deluge pulse amid ongoing nitrogen press may generate lagged responses, independent from initial responses. Collectively, this work establishes that interacting pulse and press resource alterations can produce large, complex, and often unforeseen effects on the structure and function of grassland ecosystems.
Keywords: pulse-press dynamics; shortgrass steppe; tallgrass prairie; resource alteration; community ecology; synergistic interaction